Pengaruh Faktor Etika Bisnis Islam dan Labelisasi Halal Terhadap Loyalitas Konsumen SR12 Skincare di Kota Bengkulu - Trianita Dewi; Esti Alfiah; Khairiah Elwardah (Economic Reviews Journal, 2025)
The purpose of this study is to determine the influence of the Islamic Business Ethics factor on Consumer Loyalty, to determine the influence of the Halal Labeling factor on Consumer Loyalty, and to determine the influence of the Islamic Business Ethics and Halal Labeling factors on the Consumer Loyalty of SR12 Skincare in Bengkulu City. This study used a quantitative method by distributing questionnaires to 64 respondents. The data analysis technique used was multiple linear regression using the IMB SPSS 26 application. The results of the research and discussion show that Islamic Business Ethics have a partial effect on consumer loyalty, Halal Labeling also has a partial effect on consumer loyalty, and Islamic business ethics have a simultaneous effect of 79.6%, while the remaining 20.4% is explained by other factors outside this research model.